The Behaviors of Ionospheric Scintillations Around Different Types of Nightside Auroral Boundaries Seen at the Chinese Yellow River Station, Svalbard - Priyadarshi, Shishir; Zhang, Qing-He; Ma, Yuzhang; Xing, Zanyang; Hu, Ze-Jun; Li, Guozhu (Frontiers in Astronomy and Space Sciences, 2018)
Dynamical nightside auroral structures are often observed by the all sky imagers (ASI) at the Chinese Yellow River Station (CYRS) at Ny-Ålesund, Svalbard, located in the polar cap near poleward edge of the nightside auroral oval. The boundaries of the nightside auroral oval are stable during quiet geomagnetic conditions, while they often expand poleward and pass through the overhead area of CYRS during the substorm expansion phase. The motions of these boundaries often give rise to strong disturbances of satellite navigations and communications. Two cases of these auroral boundary motions have been introduced to investigate their associated ionospheric scintillations: one is Fixed Boundary Auroral Emissions (FBAE) with stable and fixed auroral boundaries, and another is Bouncing Boundary Auroral Emissions (BBAE) with dynamical and largely expanding auroral boundaries. Our observations show that the auroral boundaries, identified from the sharp gradient of the auroral emission intensity from the ASI images, were clearly associated with ionospheric scintillations observed by Global Navigation Satellite System (GNSS) scintillation receiver at the CYRS. However, amplitude scintillation (S4) and phase scintillation (σφ) respond in an entirely different way in these two cases due to the different generation mechanism as well as different IMF (Interplanetary Magnetic Field) condition. S4 and σφ have similar levels around the FBAE, while σφ was much stronger than S4 around BBAE. The BBAE were associated with stronger particle precipitation during the substorm expansion phase. IU/IL, appeared to be a good indicator of the poleward moving auroral structures during the BBAE as well as FBAE.